Schiță de indicatori ai calității vieții - Mărginean, Ioan (Calitatea Vieții, 1991)
For an adequate understanding of the peoples' way of living and quality of life, it is necessary to use a diversified range of indicators, which must take into account not only the global elements but also the aspects related to the family, own life, the satisfaction/insatisfaction degree of life, the subjective dimension of the extant situation perception. Beginning with the definition of the quality of life as a mood and a desirable object and with the theoretical and practical research (through the diagnosis means) of this field of interest, the author has selected a number of 100 indicators of the quality of life, having in view their relevance and their properties of interchangeability and synthesis.